Implementation of Two Stage Isolated Multilevel Inverter Con-trol Strategy Using Fuzzy Logic Controller for Photovoltaic Application - Gowd, K. Jithendra; Pavani, K.; Nagabhushanam, 3K. (International Journal of Engineering and Technology, 2018)
The Photovoltaic (PV) is an unavoidable segment in renewable energy based power generation system. The two stage power conversion is a best pay tribute to grid-connected PV systems. Nevertheless, the power converters design and control integration must be prized to achieve the efficiency and reliability. In this paper, the implementation of control strategy for dual stage inverter is presented using fuzzy logic controller (FLC) along the higher frequency isolation which is galvanized. Dual stage converter contains the DC-DC converter which is three phase series resonance converter which functions as switch frequency of converter is equal to the resonance frequency. The DC-DC converter mainly provides a bus along with voltage balancing on multilevel converter. Another stage of dual stage inverter is DC-AC arrangement that comprises of a NPC (Neutral Point Clamped) inverter which is intended to inject current into the grid. The operating stages of inverter provideÂ the internalÂ transfer function, and also the external transferÂ function was obtained by considering the reverse energy flow. Dual-stage inverter with FLC is simulated and tested, resulting in lower Total Harmonic Distortion (THD).